Antibiotic resistance: knowledge, attitudes, and prescribing behaviors among dental students: a cross-sectional study - Danadneh, Mayar; Saleh, Raghad; Kwaik, Aya Abu; Lafi, Razan Abu; Yasin, Amin; Saafeen, Ghaida; Alwahidi, Mazen; Thompson, Wendy; Kateeb, Elham (Frontiers in Oral Health, 2025)
BackgroundAntimicrobial resistance (AMR) is a global crisis exacerbated by inappropriate antibiotic use, including in dentistry. This study evaluates the knowledge, attitudes, and prescribing behaviours of Palestinian dental students to identify gaps and inform educational interventions.MethodsA cross-sectional study was conducted among 4th, 5th, and internship-year dental students from four Palestinian dental schools. A validated online survey assessed knowledge, attitudes, confidence, and prescribing behaviours. Statistical analyses, including chi-square tests and Pearson correlations, examined associations between knowledge, confidence, and prescribing practices.ResultsAmong 586 participants (38% response rate), 72.2% recognized antibiotic misuse as a resistance driver, yet only 40.3% felt confident in prescribing decisions. Inappropriate prescribing was reported, with 13.3% prescribing antibiotics daily due to diagnostic uncertainty (χ2 = 504.414, p = 0.000) and 12.1% due to patient expectations (χ2 = 670.491, p = 0.000). Higher perceived knowledge correlated with reduced prescribing frequency (χ2 = 82.650, p = 0.000), and confidence in guidelines was positively associated with responsible prescribing (χ2 = 79.656, p = 0.000). Access to prescribing guidelines significantly reduced antibiotic misuse (χ2 = 106.441, p = 0.000). Interns prescribed antibiotics more frequently than juniors (χ2 = 55.618, p = 0.000).ConclusionsSignificant gaps in knowledge, confidence, and prescribing behaviours among Palestinian dental students highlight the urgent need for enhanced antibiotic stewardship education. Implementing targeted interventions, standardized guidelines, and improved access to prescribing resources is essential to promote responsible antibiotic use and combat AMR in dentistry.